Global burden of polycystic ovary syndrome in women of reproductive age, 1990–2021: Analysis of the global burden of disease study 2021 with projections to 2050 - Xinkuo Zheng; Meishen Liu; Zhaohui Bai; Ling Wu; Lili Geng; Yun Shen; Jing Na; Haonan Qiu; Yalin Xi (PLoS ONE, 2025)
Objective To evaluate the global burden of polycystic ovary syndrome (PCOS) among women of reproductive age from 1990 to 2021. Methods This study analyzed population-based data from the Global Burden of Disease (GBD) database on the incidence, prevalence, and disability-adjusted life years (DALYs) of PCOS in reproductive-aged women. Age-standardized rates for incidence (ASIR), prevalence (ASPR), and DALYs (ASDR) were calculated per 100,000 population, with 95% uncertainty intervals (UIs). Data from 204 countries and territories were stratified by age, location, and socio-demographic index (SDI). Results Globally, the burden of PCOS among reproductive-aged women in 2021 was characterized by ASIR of 64.44 (95% UI: 39.07, 103.40) per 100,000 population, ASPR of 3364.53 (95% UI: 2395.08, 4681.81) per 100,000 population, and ASDR of 29.51 (95% UI: 13.09, 61.49) per 100,000 population. Moreover, the pace of increase in ASIR, ASPR, and ASDR accelerated during 1990–2021, with estimated annual percentage change (EAPC) of 0.65 (95% CI: 0.62, 0.69), 0.74 (95% CI: 0.70, 0.77), and 0.72 (95% CI: 0.68, 0.76), respectively. Among the five SDI regions, the middle SDI region exhibited the highest EAPCs for incidence (1.39; 95% CI: 1.34, 1.43), prevalence (1.39; 95% CI: 1.34, 1.43), and DALYs (1.73; 95% CI: 1.69, 1.78). Regionally, the High-income Asia Pacific region demonstrated the highest ASIR of 308.16 (95% UI: 485.83, 171.53) per 100,000 population. At the national level, Japan exhibited the highest ASIR of 360.92 (95% UI: 199.08, 573.59) per 100,000 population. Conclusion The global burden of PCOS among women of reproductive age has shown a consistent upward trend in incidence, prevalence, and DALYs. A comprehensive understanding of the epidemiology of PCOS among women of reproductive age is essential for informing targeted prevention strategies and optimizing disease control measures.